Under beredskap och krig Nation, kön, främlingskap och våld hos svenska kvinnliga 1940-talsförfattare - Järvstad, Kristin (Kriterium, 2022)
Military preparedness and war have so far been regarded as the domain of male authors in Swedish literature, especially at the time of the Second World War. But what happens if we turn our attention to the female authors of the 1940s? Kristin Järvstad's study shows how their texts as well focus to a large extent on subjects related to military preparedness and war. A variety of topics can be found in the novels by the female writers, ranging from stories about female air guards who protect the Swedish border to female pacifists who find it necessary to kill for the sake of peace. The soldier figure in these texts also takes a radical stand when he as a deserter lays down his arms to protest against the war. In addition, one of the most charged subjects of the time linked to gender is treated from a unique perspective: the women who consort with the occupying enemy are pictured without the condemning attitude that characterizes the period in general. The most urgent question, however, concerns alienation, linked to race: who is actually included in the Swedish nation? Here, the texts display a scathing critique of the narrow-minded Swedes and the anti-Semitism that flourishes at that time. By analysing female authors' depictions of the 1940s, During Military Preparedness and War deepens the previous picture of this period in Swedish literature. The writers explored in this investigation express a profound and often critical commitment to the issue of war and violence, linked to gender and alienation. The most radical literary message of the period can also be found among their novels: the demand for the dissolution of the militaristic and patriarchal nation which strives to expand its territory without regard for human life.